Lithium Toxicity Induced Complete Heart Block: A Case Report - Muhammad Nur Azmi Baharuddin (Journal of Clinical and Health Sciences, 2026)
Lithium is traditionally used as a mood stabiliser for the treatment of bipolar disorder. Despite its proven effectiveness, it has a narrow therapeutic index. Lithium intoxication presents with a spectrum of clinical manifestations that is directly proportional to the serum lithium level. It ranges from mild gastrointestinal symptoms to more severe cardiovascular manifestations. We report a case of a 79-year-old male with underlying bipolar disorder who presented with unstable complete heart block following lithium intoxication. He was started on transcutaneous pacing in the emergency department (ED) and later underwent haemodialysis. The complete heart block resolved together with the normalisation of the serum lithium. Lithium causes cardiotoxicity through various mechanisms, including competition with electrolytes involved in cellular membranes. Haemodialysis remains the mainstay of severe lithium toxicity. Prompt recognition is crucial as patients can present with various cardiac manifestations after lithium toxicity, particularly in elderly patients, due to their underlying comorbidities.